2020
DOI: 10.31248/rjfsn2019.088
|View full text |Cite
|
Sign up to set email alerts
|

Proximate analysis of fruits and vegetables wastes from Nairobi County, Kenya

Abstract: Proximate analysis of twenty fruits and vegetable waste from Nairobi County was evaluated. They were obtained from Kangemi and Wakulima markets. Standard procedures were used for the analysis of crude fat, protein, fiber, carbohydrates, moisture, ash, nitrogen-free extract and energy. The results obtained revealed that moisture content was in the range of 82.8 to 95.86% apart from sweet potato and banana which was 62.05 and 74.30% respectively. Protein range was between 0.57 to 3.49% with high-fat content bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…The low carbohydrate, moderate lipid, and protein levels were noticeable in the derivative energy contents for the whole C. limon in this study. The energy values for the whole C. limon and C. clementina fruits in our study were higher compared to the ones reported for fruits and vegetable wastes, which ranged from 3.06 to 40.00% (Kamau et al, 2020). However, the energy values for the whole C. limon and C. clementina fruits were lower compared to the energy contents of some vegetables (248.8-307.1%) reported by Isong et al (1999).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The low carbohydrate, moderate lipid, and protein levels were noticeable in the derivative energy contents for the whole C. limon in this study. The energy values for the whole C. limon and C. clementina fruits in our study were higher compared to the ones reported for fruits and vegetable wastes, which ranged from 3.06 to 40.00% (Kamau et al, 2020). However, the energy values for the whole C. limon and C. clementina fruits were lower compared to the energy contents of some vegetables (248.8-307.1%) reported by Isong et al (1999).…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, carbohydrates are also very vital for supplying glucose for brain functioning. The carbohydrate content in the whole C. clementina fruits from the present study was higher compared to fruit and vegetable wastes from cucumber (2.17%), coriander (2.16%), tomatoes (2.93%), and spinach (2.38%) as reported by Kamau et al (2020). The low level of carbohydrate content in the whole C. limon was comparable to courgette fruit (1.99%) reported by Kamau et al (2020).…”
Section: Discussionsupporting
confidence: 55%
“…Nitrogen free extract (NFE) in proximate analysis represents sugars and starch and is obtained by difference rather than by measurement. NFE represents soluble carbohydrates (JM et al, 2020). Diet T3 (47.9%) had the lowest (p<0.05) NFE content, while T1 (68.2%) and T2 (64.6%) had higher NFE contents.…”
Section: Proximate Composition Of Sorghum-based Formulationsmentioning
confidence: 97%
“…However, the elementary composition of the flies used in the analysis remained the same for both systems and was sourced from the literature. The number and assumed weight of the BSF are the same for both systems and were derived from studies conducted by Dortmans et al and Gougbedji et al [13,37]. The BSFL output for both systems is based on the data acquired from the case study.…”
Section: Bsf Bsfl Production and Breedingmentioning
confidence: 99%